Pengembangan kurikulum Pendidikan Agama Islam (PAI) berbasis merdeka belajar dalam membentuk profil pelajar Pancasila - ardiwati, diva aliyah (Maliki Interdisciplinary Journal, 2026)
The development of an Islamic Religious Education (PAI) curriculum based on the Merdeka Belajar concept is an effort to support the formation of the Pancasila Student Profile in accordance with national education goals. This article aims to explain the role and strategies of developing a Merdeka Belajar-based PAI curriculum in shaping students who are religious, creative, independent, tolerant, and critical thinkers. The method used in this article is a literature study by reviewing various relevant journals and scientific sources. The results show that the implementation of the Merdeka Belajar-based PAI curriculum is able to create a more flexible, innovative, and student-centered learning process. In addition to improving religious understanding, PAI learning also plays a role in instilling the values of the Pancasila Student Profile through contextual and project-based learning activities. Although there are still several challenges in its implementation, the development of the Merdeka Belajar-based PAI curriculum is considered effective in forming a religious, character-driven generation capable of facing modern developments.